Extending depth of field and dynamic range from differently focused and exposed images - Qian, Qinchun; Güntürk, Bahadır Kürşat (Springer, 2016)
Focus stacking and high dynamic range (HDR) imaging are two paradigms of computational photography. Focus stacking aims to produce an image with greater depth of field (DOF) from a set of images taken with different focus distances; HDR imaging aims to produce an image with higher dynamic range from a set of images taken with different exposure values. In this paper, we present an algorithm which combines focus stacking and HDR imaging in order to produce an image with both extended DOF and dynamic range from a set of differently focused and exposed images. The key step in our algorithm is focus stacking regardless of the differences in exposure values of input images. This step includes photometric and spatial registration of images, and image fusion to produce all-in-focus images. This is followed by HDR radiance estimation and tonemapping. We provide experimental results with real data to illustrate the algorithm.
WOS: 000371808500011
Keywords: High Dynamic Range Imaging; Focus Stacking; Photometric and Spatial Registration